Pendekatan Metode ISMO Dalam Menyusun Penjadwalan Perawatan Gearbox dan Rantai Pengangkut Ore Departemen Circular Sintering PT. IRNC - Wirakusuma, Kadex Widhy; Purba, Ari Pranata Primisa; Muhammad, Katon (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2023)
PT. IRNC is a company that operates in the smelter industry. One of the company's production processes is to produce and distribute raw materials in the form of wet Ore into iron and steel products. The distribution of raw materials in this company is continuously ongoing, leading to frequent failures in the functions of the gearbox and the chain of transportation of mineral raw materials. The company has a bustling machine activity but is not associated with the preventive maintenance activities of the machine. One of the activities that can solve the maintenance problem is scheduling preventative maintenance activities and periodic repairs to the gearbox and chain carrier of raw materials. Preventive maintenance is the maintenance activity on the machine which has the purpose of preventing the occurrence of damage, or the maintenance method for the machine planned for the prevention to extend the life of the machine as well as to avoid the failure of function on the machinery that may occur during the production process. This research aims to provide recommendations for scheduled maintenance of the machine with a preventive maintenance approach with the ISMO Method. The results of the research carried out based on the type of work performed inspection (I) and small repair (S) obtained results respectively for gearbox 13 times inspections (I), and 21 times small repairs (S), while for the chain of transportation of Ore 8 times inspection and four times small reparations, and the number of workers involved 21 people, with the total labor costs of Rp—863,820 million per year.